Implementation of Software Defined Networking (SDN) Technology in the Campus Network of Ichsan Sidenreng Rappang University - Baharuddin Baharuddin (Pt. Anagata Sembagi Education, 2025)
The development of information technology and the digitalization of higher education demand a more efficient, flexible, and secure network infrastructure. Software Defined Networking (SDN) offers a new paradigm in network management by separating the control plane and data plane, enabling more centralized and adaptive network management. This study aims to analyze the implementation of SDN in campus networks, specifically at Ichsan Sidenreng Rappang University, and identify its benefits, challenges, and implementation strategies. The method used is a systematic literature review of 15 scientific publications from 2020-2025 that discuss the implementation of SDN in the context of campus networks. The results show that SDN provides significant network performance improvements, with a decrease in latency from 37.7 ms to 18 ms, jitter from 40.3 ms to 2.7 ms, and an increase in throughput from 95 Mbps to 98.2 Mbps compared to conventional networks. SDN also increases flexibility through centralized management and automation, strengthens security with adaptive firewall integration, and improves service redundancy and availability. Key implementation challenges include the need for human resource training, the development of comprehensive security policies, and testing on more complex topologies. This study concludes that implementing SDN on campus networks is strategic for supporting the digitalization of higher education, with recommendations for thorough planning, ongoing human resource training, and the development of policies that holistically integrate technical and security aspects.